Participatory Development of Mae Soon Noi Bank Wisdom at Fang District, Chiang Mai Province - Tongngam, Pataravadee; Wongthep, Wanchaiyut; Jariyangamwong, Sutthapreecha; Janevinitchai, Noppadol (Area Based Development Research Journal, 2022)
The coronavirus epidemic (COVID-19) has led to unexpected unemployment issues in Ban Mae Soon Noi, Fang District, Chiang Mai Province, in which low-income groups struggled to meet their basic needs. To make a living, these unemployed have been involved in encroachment into restricted areas of mixed deciduous forest and pine woods. This academic service, thus, aims to improve knowledge and enhance professional competence following community aptitude and potential; to provide the locals with opportunities to learn new skills, to upskill in a new context; and to promote individual professional skills. The study consists of these steps: 1) recognizing the existing problematic issues; 2) developing local economies; 3) designing community wisdom with a participatory approach; 4) taking part in enhancing the neighborhood; 5) establishing metrics and policies for use, and 6) giving the Ban Mae Soon Noi community control of the territory. As a result, 27 among the total of 78 people experiencing sudden unemployment have a new job, which helps reduce the unemployment to 51 people. Seven organizations are formed to sell products at Ban Mae Soon Noi Wisdom Resources Bank, and three new community resourceful people are recognized. These numerous initiatives allow residents to participate and observe direct financial gains. Community awareness is raised on individual values. In conclusion, the community’s architecture, forestry resources, and watersheds, to name but a few, are changing in a tangible way which will lead to a holistic change in the community.